Notes on distribution, variation and characterization of Erythrolamprus pseudocorallus Roze, 1959 (Serpentes: Colubridae) with the first records from Colombia - Curcio, Felipe Franco; Sánchez-Pacheco, Santiago J.; Mueses-Cisneros, Jonh Jairo; Rodrigues, Miguel Trefaut (Zootaxa, 2009)
The Maracaibo false coral snake Erythrolamprus pseudocorallus, previously known only from Venezuela, is recorded from five departments in Colombia. These new data include the westernmost and the southernmost records presently known for the species. Two specimens previously identified as E. aesculapii, from the localities of El Valle, Distrito Federal, Venezuela, and Yarumal, Antioquia, Colombia, are now attributed to E. pseudocorallus, the first one representing the northeasternmost record of the species. Morphological characterization of E. pseudocorallus is expanded based on the new specimens.